Issuance of Central Bank Securities : International Experiences and Guidelines - Gray, Simon (IMF Working Papers; Working Paper ;, 2015)
The paper discusses the reasons for central bank (CB) issuance of securities, and reasons for choosing different approaches e.g. in maturities and target market. It provides evidence on the range of different approaches taken by those CBs which do issue, as well as suggesting reasons why some CBs do not; and provides operational guidelines on the major building blocks of the issuance of CB securities.